2019
DOI: 10.1007/s00392-019-01549-0
|View full text |Cite
|
Sign up to set email alerts
|

Association between anemia and hematological indices with mortality among cardiac intensive care unit patients

Abstract: Background Anemia and elevated red cell distribution width (RDW) or mean corpuscular volume (MCV) are associated with an adverse prognosis in patients with cardiovascular disease and critical illness. Limited data exist regarding these associations in unselected cardiac intensive care unit (CICU) patients. Methods Retrospective cohort study of CICU patients between January 1, 2007, and December 31, 2015, with a hemoglobin (Hb) level measured at admission. Multivariable regression was performed to determine pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 31 publications
(53 reference statements)
0
20
1
Order By: Relevance
“…These patients had higher resource utilization and short-term mortality in the unmatched cohort and higher resource utilization in the propensity-matched cohort, suggesting that PAC use is a marker for greater illness severity. 41,42 As noted in our study, in admissions within the non-PAC cohort, RHC was used in those with greater severity, without any differences in outcomes. Smaller studies have shown the use of a PAC to be associated with improved survival in CS because of any aetiology.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…These patients had higher resource utilization and short-term mortality in the unmatched cohort and higher resource utilization in the propensity-matched cohort, suggesting that PAC use is a marker for greater illness severity. 41,42 As noted in our study, in admissions within the non-PAC cohort, RHC was used in those with greater severity, without any differences in outcomes. Smaller studies have shown the use of a PAC to be associated with improved survival in CS because of any aetiology.…”
Section: Discussionmentioning
confidence: 88%
“…Demographic characteristics, hospital characteristics, acute organ failure, coronary angiography, percutaneous coronary interventions (PCI), and mechanical circulatory support (MCS) use were identified for all admissions using previously used methodologies from our group. [2][3][4][5]8,9,[28][29][30][31][32][33][34][35] Acute noncardiac organ failure was classified as respiratory (acute respiratory failure, other pulmonary insufficiency, acute respiratory distress syndrome, respiratory arrest, and ventilator management), renal (acute kidney injury), and hepatic (acute hepatic failure, hepatic encephalopathy, hepatic infection, and hepatitis unspecified), hematologic (defibrination syndrome, acquired coagulation factor deficiency, coagulation defect, and thrombocytopenia), and neurologic (anoxic brain injury, acute encephalopathy, coma, altered consciousness, and electroencephalogram). [3][4][5]9,30,32 Similar to prior literature from the HCUP-NIS, we used the procedure day for RHC/PAC placement to time concomitant coronary angiography, PCI, MCS, and invasive mechanical ventilation.…”
Section: Study Population Variables and Outcomesmentioning
confidence: 99%
“…Furthermore, comparable reports are found about the RDW and mortality. [25] described, in their investigation on 9644 patients coming to a cardiac intensive care unit for admission, an independent association between RDW and hospital mortality. In addition, the RDW seems to be a prognostic marker for 30day mortality in severe sepsis [26].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, comparable reports are found about the RDW and mortality. [25] described, in their investigation on 9644 patients coming to a cardiac intensive care unit for admission, an independent association between RDW and hospital mortality. In addition, the RDW seems to be a prognostic marker for 30-day mortality in severe sepsis [26].…”
Section: Discussionmentioning
confidence: 99%